NiFe2 and its nitride γ-NiFe2N derived from NiFe2O4: Magnetostriction, thermal expansion, resistivity and corrosion resistance. (May 2017) - Sun, X.; Zhu, X.; Ruan, Y.R.; Ding, Z.L.; Song, W.H.; Zhao, B.C.; Ma, Y.Q.
Graphical abstract: The perovskite γ-NiFe2 N with the face centered cubic symmetry, rather than the hexagonal symmetric ɛ-NiFe2 N in previous report, was synthesized based on the route from NiFe2 O4 to NiFe2 and finally to γ-NiFe2 N. γ-NiFe2 N presents the enhanced magnetization (a), magnetostriction (b) and resistivity (d); it exhibits the negative thermal expansion in two temperature windows below 60 K and between 235 K and 305 K (c). Furthermore, γ-NiFe2 N has the better corrosion resistance in the sodium chloride aqueous solution than NiFe2, as shown in the SEM images (e) and (f). The unique properties and low-cost of γ-NiFe2 N may find applications somewhere. Highlights: The perovskite γ-NiFe2 N, instead of ɛ-NiFe2 N in previous reports, was synthesized. γ-NiFe2 N has better thermal stability than ɛ-NiFe2 N. γ-NiFe2 N presents improved magnetostriction, resistivity and corrosion resistance. The unique properties and low-cost of γ-NiFe2 N may find applications somewhere. We revealed the correlation between structure and magnetic/thermal/electronic properties. Abstract: γ-NiFe2 N with the face centered cubic symmetry, rather than the hexagonal symmetric ɛ-NiFe2 N in previous reports, was synthesized by treating NiFe2 alloy in an ammonia atmosphere. Compared with the NiFe2 sample, the γ-NiFe2 N exhibited the strong ferromagnetism, giant magnetostriction, high resistivity and good corrosion resistance. The unique properties of γ-NiFe2 N expand its applications. Besides, as a magnetostriction material, γ-NiFe2 N does not contain any resource-critical rare-earth elements and it is over ten times lower cost than the rare-earth doped Galfenol or Terfenol-D alloys because Ga, Tb or Dy is very expensive.